The Development of Learning Media Oriented to Team Games Tournament Learning Model Using Canva and Kahoot! to Improve Student™s Problem Solving Ability in SMAN 10 Medan - Paula Putri Vansia Br. Siahaan; Hamidah Nasution (Jurnal Fibonaci: Jurnal Pendidikan Matematika, 2022)
This study aims to determine (1) the process of developing learning media based on Canva and Kahoot, (2) learning media can be used for the learning process, and (3) improving the problem solving ability of students who are given mathematics learning with the topic of developed arithmetic series. The subjects in this study were students of class XI IPA -1 SMA NEGERI 10 MEDAN. Learning tools developed in the form of learning media using Canva and Kahoot!. Data analysis techniques in the development of learning tools used descriptive statistical analysis techniques. The results showed that: (1) the learning media development process involved five stages of development and then before being tested in the field, validation was obtained with the media assessment average score from the media expert team was 3.2 (valid) and material expert was 3.45 (valid). , based on the efficiency aspect based on the results of the student response questionnaire, the first trial obtained a score of 72% (positive) and the second trial was carried out with revisions and got a score of 85% (very positive), and based on the effectiveness of the learning tools developed on the problem solving abilities of students concluded on: student learning completeness after the use of media by 85%; (2) with the previous description the media can be used as a learning aid with revisions, and (3) the improvement of problem solving abilities can be seen from the n-Gain value of 0.5 which means it is in the medium category